The education of Polish children deported to the USSR and evacuated to the near and Middle East during World War II - Roguska, Agnieszka; Roguski, Rafał; Madej, Anna (Przegląd Wschodnioeuropejski, 2024)
The text describes fragmentary education gained by children deported from the territory of Poland occupied by the Soviet Union to the forced labour camps and kolkhozes. They were subsequently evacuated from the USSR to Iran and other countries controlled by Great Britain. The release of such a large group of people from Gulag camps and places of isolation was an unprecedented situation in the Soviet system, and the presence of such a large number of civilians along the regular military units being formed at the time was unexampled in history. The authors illustrate education methods and conditions of Polish youth released with their families from Gulag camps and locations of compulsory labour together under the so-called amnesty. They provide details regarding the young refugees’ health issues, numerous cases of starvation to death or symptoms of post-traumatic stress (PTSD ‒ post-traumatic stress disorder). They present the problems with the evacuation itself and confront the standards of living and expulsion from Soviet Russia with a highly positive reception of refugees on the Persian land. They indicate their further fate, including the creation of orphanages and schools, as children in the USSR were deprived of the opportunity to learn. It was important to depict extremely difficult, frequently provisional attempts at schooling Polish youngsters against the background of historic events.